2021
DOI: 10.1111/gcb.15659
|View full text |Cite
|
Sign up to set email alerts
|

Statistical upscaling of ecosystem CO2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties

Abstract: The regional variability in tundra and boreal carbon dioxide (CO2) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO2 fluxes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 111 publications
6
103
1
Order By: Relevance
“…Overall, the simulated pan-arctic carbon fluxes are systematically lower than other published values (Efren et al, 2019;Rawlins et al, 2015;McGuire et al, 2012). Virkkala et al (2021) estimate an annual NEE in the range of −46 to +10 g C m −2 yr −1 , while our simulations have a mean estimate around −35.5 g C m −2 yr −1 (see Table 2).…”
Section: Impact On Physical and Biogeochemical Variablescontrasting
confidence: 75%
See 1 more Smart Citation
“…Overall, the simulated pan-arctic carbon fluxes are systematically lower than other published values (Efren et al, 2019;Rawlins et al, 2015;McGuire et al, 2012). Virkkala et al (2021) estimate an annual NEE in the range of −46 to +10 g C m −2 yr −1 , while our simulations have a mean estimate around −35.5 g C m −2 yr −1 (see Table 2).…”
Section: Impact On Physical and Biogeochemical Variablescontrasting
confidence: 75%
“…Despite numerous field-based and modelling efforts to date, it is still uncertain whether the Arctic will act as a carbon source or sink in the future (McGuire et al, 2012;Virkkala et al, 2021). The predicted future carbon balance varies widely among models -between a loss of 641 Pg C A.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity analyses, manipulated field experiments, and model simulations all consistently show that the fixation of CO 2 by plants outpaces the potential loss of CO 2 from permafrost and accelerated plant respiration in current conditions. The fixation of CO 2 by vegetation has also led to an accumulation of soil CO 2 (6) in the surface layers across the Tibetan Plateau, as shown by 137 Cs- 14 C dating (44,45), 137 Cs-140 Pb ex dating (46), and a repeatsampling approach (6), reporting a net soil C accumulation of 25 to 113 g C m −2 y −1 . Together, these methods have reported an average net soil C accumulation rate of 53.6 g C m −2 y −1 based upon isotope dating, indicating that roughly half of the C newly fixed by plants is stored in soils.…”
Section: Ecologymentioning
confidence: 99%
“…A recent study showed that the Pan-Arctic permafrost is a net CO 2 source of 630 Tg C y −1 (12), albeit with strong uncertainties (range: 15 to 975 Tg C y −1 ). By contrast, a synthesis study and model simulations reported that the Arctic can act as a CO 2 sink at the ecosystem level (8,13,14), given that the uptake of CO 2 by plants is accelerating as a result of Arctic greening. These contrasting results reveal the large uncertainties in feedbacks to the present-day warming climate across Arctic permafrost ecosystems.…”
mentioning
confidence: 96%
“…An inconsistent regional estimation of carbon sink and/or source potentials under a warming climate has been reported for regions of degrading permafrost with varied ecosystem types. Virkkala et al (2021) estimated the boreal regions as a carbon sink based on a net ecosystem exchange (NEE) of −46 g C m −2 yr −1 , because of the photosynthetic offset of the released CO 2 (soil respiration) [81] and the Arctic tundra served as a carbon source at 10 g C m −2 yr −1 [82]. In the High-Arctic semi-desert regions, the carbon sink could strengthen by an order of magnitude under a warmer-wetter climate, but the summer carbon sink could be reduced by 55% under just a warming treatment [83].…”
Section: Atmospheric Ch 4 and Co 2 Emission Induced By Permafrost Degradationmentioning
confidence: 99%